Peak physical demands of elite women's soccer: Assessing playing position and post-goal locomotor patterns - Datson, N.; Dello Iacono, A.; Doncaster, G.; Page, R. M.; McKeown, A.; Unnithan, V. B. (International Journal of Sports Science & Coaching, 2024)
It has recently been identified that the assessment of peak periods of activity better considers the stochastic nature of match-play and the influence that contextual factors have on these peak periods. Limited research exists attempting to link the tactical and physical aspects of performance, especially in female players. Therefore, the current study aimed to assess post-goal locomotor patterns and positional differences on peak match demands in elite female soccer players. Using 10 Hz global positioning system units, a total of 133 player match observations were recorded from 14 matches played by an elite Scottish women's professional soccer team. The total distance (TD), high-speed running distance (>18 km/h) (HSRD) and PlayerLoad™ (PL) were assessed for 1, 3 and 5-minute peak periods using a rolling epoch approach. Playing position and post-goal activity were used as modulating factors. Linear mixed models established a main effect for playing position for the HSRD at peak 1-minute (p<.001), 3-minute (p < .001) and 5-minute (p < .001) epochs. There were also main effects for the playing position for TD at peak 1-minute (p= .001) and PL at peak-3minute (p = .002). Team-level data showed a main effect for condition (score vs. concede) for 3-minute TD data and main effects for time (pre vs. post) for 1,3 and 5-minute epochs for PL data. The average and peak values were shown to differ across playing positions for all variables. Likewise, potentially indicative of tactical adjustments significant differences were observed at both a team and player level following scoring or conceding a goal.